A nanopoint Schottky-gate array device: surface defect application and molecular detection1. Issue 22 (11th March 2015) - Sung, Chun-Han; Chien, Tzu-Chiao; Chang, Chih-Ming; Chang, Chien-Min; Yeh, Ping-Hung
<x xml:space="preserve">Abstract</x> Nanopoint Schottky-gate array devices (NPSGAD) can considerably enhance the sensitivity, the signal current output level and the gas levels distinguishability.